V-A ECMO for neonatal coxsackievirus B fulminant myocarditis: a case report and literature review - Li, Xingchao; Sun, Li; Xi, Shibing; Hu, Yaofei; Yu, Zhongqin; Liu, Hui; Sun, Hui; Jing, Weili; Yuan, Li; Liu, Hongyan; Li, Tao (Frontiers in Cardiovascular Medicine, 2024)
Background Neonatal (enteroviral) myocarditis (NM/NEM) is rare but unpredictable and devastating, with high mortality and morbidity. We report a case of neonatal coxsackievirus B (CVB) fulminant myocarditis successfully treated with veno-arterial extracorporeal membrane oxygenation (V-A ECMO). Case presentation A previously healthy 7-day-old boy presented with fever for 4 days. Progressive cardiac dysfunction (weak heart sounds, hepatomegaly, pulmonary edema, ascites, and oliguria), decreased left ventricular ejection fraction (LVEF) and fractional shortening (FS), transient ventricular fibrillation, dramatically elevated creatine kinase-MB (405.8 U/L), cardiac troponin I (25.85 ng/ml), and N-terminal pro-brain natriuretic peptide (NT-proBNP > 35,000 ng/L), and positive blood CVB ribonucleic acid indicated neonatal CVB fulminating myocarditis. It was refractory to mechanical ventilation, fluid resuscitation, inotropes, corticosteroids, intravenous immunoglobulin, and diuretics during the first 4 days of hospitalization (DOH 1–4). The deterioration was suppressed by V-A ECMO in the next 5 days (DOH 5–9), despite the occurrence of bilateral grade III intraventricular hemorrhage on DOH 7. Within the first 4 days after ECMO decannulation (DOH 10–13), he continued to improve with withdrawal of mechanical ventilation, LVEF > 60%, and FS > 30%. In the subsequent 4 days (DOH 14–17), his LVEF and FS decreased to 52% and 25%, and further dropped to 37%–38% and 17% over the next 2 days (DOH 18–19), respectively. There was no other deterioration except for cardiomegaly and paroxysmal tachypnea. Through strengthening fluid restriction and diuresis, and improving cardiopulmonary function, he restabilized. Finally, notwithstanding NT-proBNP elevation (>35,000 ng/L), cardiomegaly, and low LVEF (40%–44%) and FS (18%–21%) levels, he was discharged on DOH 26 with oral medications discontinued within 3 weeks postdischarge. In nearly three years of follow-up, he was uneventful, with interventricular septum hyperechogenic foci and mild mitral/tricuspid regurgitation. Conclusions Dynamic cardiac function monitoring via real-time echocardiography is useful for the diagnosis and treatment of NM/NEM. As a lifesaving therapy, ECMO may improve the survival rate of patients with NM/NEM. However, the “honeymoon period” after ECMO may cause the illusion of recovery. Regardless of whether the survivors of NM/NEM have undergone ECMO, close long-term follow-up is paramount to the prompt identification and intervention of abnormalities.